A New Report of Floral Modification in Leucas aspera (Willd.) Link from Jalpaiguri District, West Bengal, India - Sarkar, Anup Kumar; Mandal, Sujay; Mazumder, Mallika; Dey, Manas (Indian Forester, 2019)
Leucas aspera (Willd.) Link (Family Lamiaceae) is an annual herb and distributed almost all parts of India and the Philippines as well as the plains of Mauritius and Java (https1). Leucas aspera is typically found in dry, open, sandy soil and is abundant in areas with waste (https2). It is very famous for its uses in the fields of medicine and agriculture (Prajapati et al., 2010; Srinivasan et al., 2011). Leucas aspera Leaves and flowers of the plants are edible. Medicinally, it has been proven to possess various pharmacological activities like antifungal, antioxidant, antimicrobial, antinociceptive and cytotoxic activity (Prajapati et al., 2010).